2012
DOI: 10.1186/1471-2474-13-95
|View full text |Cite
|
Sign up to set email alerts
|

Total hip arthroplasty: leg length inequality impairs functional outcomes and patient satisfaction

Abstract: BackgroundLeg length inequality (LLI) was identified as a problem of total hip arthroplasty soon after its introduction. Leg lengthening is the most common form of LLI. Possible consequences are limping, neuronal dysfunction and aseptic component loosening. LLI can result in an increased strain both on the contralateral hip joint and on the abductor muscles. We assessed the influence of leg lengthening and shortening on walking capacity, hip pain, limping and patient satisfaction at 2-year follow-up.Methods478… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 32 publications
(33 reference statements)
2
60
1
1
Order By: Relevance
“…A large study on patients having undergone hip arthroplasty (n=753) shows that leg length discrepancy reduces satisfaction and functional outcome after hip arthroplasty. 47 Reducing risks of falls reduces the degree of disability of amputees by improving their mobility and hence improves their quality of life. 48…”
Section: Discussionmentioning
confidence: 99%
“…A large study on patients having undergone hip arthroplasty (n=753) shows that leg length discrepancy reduces satisfaction and functional outcome after hip arthroplasty. 47 Reducing risks of falls reduces the degree of disability of amputees by improving their mobility and hence improves their quality of life. 48…”
Section: Discussionmentioning
confidence: 99%
“…Farmer et al [28] found that treatment of hip pain after THA in patients with LLD was more difficult than in those who had no LLD. Röder et al [30] reported a negative effect of leg lengthening after THA on walking capacity, limping and patient satisfaction and of leg shortening, on hip pain, limping and patient satisfaction. Therefore, the shortening of the operated leg in this study population did not seem to compromise the prosthetic stability.…”
Section: Discussionmentioning
confidence: 99%
“…However, these relationships vary between biological tissues and the degenerative state of the tissue. Equivalent experiments were done on intervertebral discs and showed that 45 to 80% of the Young’s modulus, the aggregate modulus, the radial permeability and the axial permeability can be explained mostly by MT and diffusion sequences [60]. On the skeletal muscle, up to 78% of the Young’s modulus can be explained by relaxation times, magnetization transfer and diffusion coefficients suggesting a linear relationship [61].…”
Section: Discussionmentioning
confidence: 99%